Right Romance : Heroic Subjectivity and Elect Community in Seventeenth-Century England - Jones, Emily Griffiths, 1983- (Cultural inquiries in English literature, 1400-1700., 2019)
"A study of romance, religion, and politics in seventeenth-century England, presenting a recontextualized understanding of romance as a multi-generic narrative structure or strategy rather than a prose genre"--